2017
DOI: 10.26822/iejee.2017131894
|View full text |Cite
|
Sign up to set email alerts
|

Improving the reading comprehension of primary-school students at frustration-level reading through the paraphrasing strategy training: A multiple-probe design study

Abstract: The purpose of this study was to investigate the effectiveness of "RAP" [RAP is a three-step strategy: Read-Ask-Put], a paraphrasing cognitive strategy training, associated with a self-regulatory model, on the development of reading comprehension among fourth-grade students. All participants were selected on the basis of initial reading comprehension measures and consisted of three male students who were identified as being at a frustration-level reading. A multiple-probe design across participants was used. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(49 reference statements)
0
11
0
3
Order By: Relevance
“…In Pilten's (2007) study, it was found that the experimental group, which was trained on how to identify main ideas, recalled more main ideas and details in texts than the control group of students who were taught with traditional reading instruction. Other research on reading comprehension strategies confirmed the practical utility of strategy teaching in developing comprehension of the main ideas and details and in the development of reading comprehension skills (Ellis and Graves, 1990;Hagaman, Casey and Reid, 2016;Hagaman and Reid, 2008;Ilter, 2017a;Lauterbach and Bender, 1995). According to these results, it can be considered that the direct instruction of the reading strategies is mediated by the poor readers.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…In Pilten's (2007) study, it was found that the experimental group, which was trained on how to identify main ideas, recalled more main ideas and details in texts than the control group of students who were taught with traditional reading instruction. Other research on reading comprehension strategies confirmed the practical utility of strategy teaching in developing comprehension of the main ideas and details and in the development of reading comprehension skills (Ellis and Graves, 1990;Hagaman, Casey and Reid, 2016;Hagaman and Reid, 2008;Ilter, 2017a;Lauterbach and Bender, 1995). According to these results, it can be considered that the direct instruction of the reading strategies is mediated by the poor readers.…”
Section: Resultsmentioning
confidence: 84%
“…Örneğin Pilten (2007) çalışmasında, okuma ödevlerinde ana fikri belirleme becerisi öğretimini alan deney grubunun geleneksel okuma öğretimine dâhil olan kontrol grubu öğrencilerine kıyasla metinlerde daha fazla ana fikir cümlelerini belirlediği tespit edilmiştir. Okuduğunu anlama stratejileri üzerine yapılan diğer çalışmalar, ana fikir ve detayların bilincine varılmasında ve okuduğunu anlama becerilerinin geliştirilmesinde strateji öğretiminin pratik yararlılığını doğrulamıştır (Ellis ve Graves, 1990;Hagaman, Casey ve Reid, 2016;Hagaman ve Reid, 2008;İlter, 2017a;Lauterbach ve Bender, 1995). Bu sonuçlara göre okuduğunu anlama stratejileri üzerine yapılan doğrudan öğretimin zayıf okuyucuların okuduğunu anlamalarına aracılık ettiği söylenebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 3 more Smart Citations